Perkembangan Usia Dini (Masa Kanak-Kanak Awal) - Al Munawaroh; Pebrienti Siregar; Rahmadani Rahmadani; Linda Yarni (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This article discusses the concept of early childhood development. Early childhood children are different, unique individuals and have their own characteristics according to their age stages. Early childhood is a golden age where stimuli from all aspects of a child's development play an important role in subsequent developmental tasks. Early childhood is the beginning of a child's life and is the most important period in an individual's life. During this period, all aspects of development including: motoric, language, cognitive, social, emotional and moral experience very rapid development so they require guidance so that all their potential develops optimally.